O „rodzeniu się” poezji w twórczości Joanny Mueller - Witczak, Krzysztof (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The essay concerns the work of Joanna Mueller, who is one of the main representatives of polish linguistic poetry. Her project combines the tradition of linguistic poetry and body experience. This strategy requires the development of a new understanding of the language, which will no longer be conceived as a trap references, but rather as one of many elements of reality. The best way to describe the work of the poet’s imagery is stratification, both in terms of the attitudes adopted by Mueller, by the subjects, to the construction of the poem. Equally important it seems to be the prospect of motherhood, both in terms of artistic activity, as well as the practices of life.